# inference problem

• Nov 24th 2009, 12:12 PM
TurboManX
inference problem
Hi,
I've been bogging down for a while but got nowhere.
Use rules of inference to show that
$
p\rightarrow\,q
$

$
q\rightarrow\ (r\wedge\ s)
$

$
\neg\ r \rightarrow\ (\neg\ t \vee\ u)
$

$
p \wedge\ t
$

-------------
$
\therefore u
$

Regards
TmX
• Nov 24th 2009, 02:10 PM
emakarov
It does not seem to follow. Consider the assignment where p, q, r, s are true and t, u are false. Then it seems to me that all premises are true but u is false.

Also, could you write an example of inference? There are dozens of way to write proofs, from completely formal to English text. I don't know what style you use.
• Nov 25th 2009, 01:08 AM
TurboManX
Ignore this post please,
Posted accidentally
• Nov 25th 2009, 01:17 AM
TurboManX
Quote:

Originally Posted by emakarov
It does not seem to follow. Consider the assignment where p, q, r, s are true and t, u are false. Then it seems to me that all premises are true but u is false.

Also, could you write an example of inference? There are dozens of way to write proofs, from completely formal to English text. I don't know what style you use.

Sure,